The Urgency of Islamic Economics Education in Building Youth to Support the Growth of Sharia Economy - Choiriyah Choiriyah; Dwi Noviani; Saprida Saprida (International Forum of Researchers and Lecturers, 2025)
This study aims to explore the urgency of Islamic economics education and its introduction to the younger generation as a means of supporting the growth of a sharia-based economy. In the global context, sharia-based business practices are increasingly accepted, even among non-Muslim communities, highlighting the importance of strengthening Islamic economic education as the foundation for developing competent human resources. This research employs a literature review approach to analyze the relevance of Islamic economics in addressing the shortcomings of conventional economic systems, which often fail to ensure societal welfare. The findings emphasize the importance of integrating Islamic economics into the education curriculum from an early age to foster comprehensive understanding. Additionally, it highlights the government's role in enhancing regulations and providing support for the development of the sharia financial industry.